2022
DOI: 10.1002/aur.2825
|View full text |Cite
|
Sign up to set email alerts
|

Resilience, and positive parenting in parents of children with syndromic autism and intellectual disability. Evidence from the impact of the COVID‐19 pandemic on family's quality of life and parent–child relationships

Abstract: Family quality of life (FQoL) outcomes collected during the first year of COVID-19 has been combined with 2018 data to estimate the outbreak's impact on parental outcomes on a sample of 230 families with syndromic autistic children and those with intellectual disabilities (IDs). Despite challenges imposed by the COVID-19 outbreak, our study found that FQoL outcomes reported by participating parents during the first year of COVID-19 appears to be similar to ratings from a prepandemic study of families with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 100 publications
1
4
0
1
Order By: Relevance
“…Second, concerning neutral effects, some mothers reported that their jobs and lives did not change, thus implying that they were not significantly affected. Third, regarding positive effects, the mothers reported that they worked out how to interact with the child, such as “provide support according to the infection situation” and “maintain a moderate psychological distance.” These results are consistent with those of Daulay (2021), who showed that mothers use coping strategies in their efforts to minimize the stress and difficulties they encounter and support the resilience model proposed by Bolbocean et al (2022). Notably, the participating mothers had a history of receiving consultations and support in clinic centers and other sources prior to the pandemic, which could have facilitated their spontaneous use of coping strategies.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Second, concerning neutral effects, some mothers reported that their jobs and lives did not change, thus implying that they were not significantly affected. Third, regarding positive effects, the mothers reported that they worked out how to interact with the child, such as “provide support according to the infection situation” and “maintain a moderate psychological distance.” These results are consistent with those of Daulay (2021), who showed that mothers use coping strategies in their efforts to minimize the stress and difficulties they encounter and support the resilience model proposed by Bolbocean et al (2022). Notably, the participating mothers had a history of receiving consultations and support in clinic centers and other sources prior to the pandemic, which could have facilitated their spontaneous use of coping strategies.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, the current findings play an important role in suggesting more creative solutions to the challenges of coping with and resilience to future crises. As noted by Bolbocean et al (2022) and Daulay (2021), maternal resilience could have prompted the children's adaptation to their daily lives during the pandemic. Furthermore, this study suggests the presence of children's coping and resilience abilities, as they demonstrated efforts to cope with and overcome the constraints in their lives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found no difference to slight deterioration in HRQoL among most of the respondents in different countries in our study. Many studies have suggested that HRQoL and mental well-being during the pandemic in the general population are persistently poorer compared to before the pandemic [ 29 , 37 , 38 , 39 ], although in certain sub-populations no changes were observed [ 40 ]. Our study results may indicate that the effects of the pandemic have persisted, even among those that have not been infected by COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…One COVID-19 specific study found that teaching parents how to engage with their children through acts of kindness, developing trusting relationships, and responding with compassion increased parent–child resilience during the pandemic as measured by parental resilience and parent-reported child empathetic prosocial behavior levels ( Johnson et al, 2022 ). Studies of children with neurodevelopmental disorders, such as autism spectrum disorder and intellectual disabilities, showed that positive parenting enhanced pandemic resilience, as measured by a family quality of life and parent–child relationship questionnaires ( Bolbocean et al, 2022 ). However, no studies have looked at whether positive parenting can specifically impact children’s behavior in a sample of children at neurological risk (i.e., preterm birth, brain injuries, pediatric stroke) and/or neurodevelopmental (i.e., learning disabilities, autism, ADHD) during and immediately following the COVID-19 pandemic, and whether parental mental health impedes positive parenting practices.…”
Section: Introductionmentioning
confidence: 99%